2002
DOI: 10.1093/oep/54.4.636
|View full text |Cite
|
Sign up to set email alerts
|

Insecure old-age security

Abstract: In this paper, we examine the old-age security hypothesis according to which parents rear children because they expect the latter to care for them in their later years. In developing countries where there are no perfect capital markets, children are usually viewed as a potential source of income and as a time-related support in old age. However, investing in children remains risky. By focusing on uncertainty about the parental consumption during old age, we show that there exists a precautionary motive for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
0
4
0
5
Order By: Relevance
“…This shift in instruments to insure income during old age has been studied in relation to fertility for the developing countries of today (for example Galasso, Gatti, & Profeta, 2009;Jellal & Wolff, 2002). Systematic studies regarding countries that were industrializing during the nineteenth century, using the same methods and types of sources for the time before and after the presumed shift, are necessary if one wants to analyze long-term changes in the relative importance of the two different alternatives.…”
Section: Previous Researchmentioning
confidence: 99%
“…This shift in instruments to insure income during old age has been studied in relation to fertility for the developing countries of today (for example Galasso, Gatti, & Profeta, 2009;Jellal & Wolff, 2002). Systematic studies regarding countries that were industrializing during the nineteenth century, using the same methods and types of sources for the time before and after the presumed shift, are necessary if one wants to analyze long-term changes in the relative importance of the two different alternatives.…”
Section: Previous Researchmentioning
confidence: 99%
“…A case in point is the benefit of relying on children for some form of care in the older ages, especially after parents retire from income-generating work. While all societies support such expectations, it has been suggested that in developing societies, this expectation may be valued quite highly and may itself fuel personal desires to have many children or to have a particular sex composition (Caldwell 1977; De Vos 1985; Jellal and Wolff 2002; Nugent 1985). The problem with such high valuations is that the children may not have the socially advantageous sex, they may die, may be economically incapable or may not be altruistic in the end; and the most productive years of children are so far into the future, it is difficult to determine fully whether such expectations will be realised when parents are actually having them.…”
Section: Introductionmentioning
confidence: 99%
“… These informal arrangements may be indirectly observed through family size, investments in children's education (Jellal and Wolff, 2002), informal old‐age security provided by children (Hoddinott, 1992), help given by older people to their children in domestic tasks, risk‐sharing agreements between family members (Kotlikoff and Spivak, 1981; Victorio, 2002), co‐residence, etc. …”
mentioning
confidence: 99%